Macrophages/Microglia Represent the Major Source of Indolamine 2,3-Dioxygenase Expression in Melanoma Metastases of the Brain - Herrera-Rios, Dayana; Mughal, Sadaf S.; Teuber-Hanselmann, Sarah; Pierscianek, Daniela; Sucker, Antje; Jansen, Philipp; Schimming, Tobias; Klode, Joachim; Reifenberger, Julia; Felsberg, Jörg; Keyvani, Kathy; Brors, Benedikt; et al. (Frontiers in Immunology, 2020)
The manifestation of brain metastases in patients with advanced melanoma is a common event that limits patient's survival and quality of life. The immunosuppressive properties of the brain parenchyma are very different compared to the rest of the body, making it plausible that the current success of cancer immunotherapies is specifically limited here. In melanoma brain metastases, the reciprocal interplay between immunosuppressive mediators such as indoleamine 2, 3-dioxygenase (IDO) or programmed cell death-ligand 1 (PD-L1) in the context of neoplastic transformation are far from being understood. Therefore, we analyzed the immunoreactive infiltrate (CD45, CD3, CD8, Forkhead box P3 [FoxP3], CD11c, CD23, CD123, CD68, Allograft Inflammatory factor 1[AIF-1]) and PD-L1 with respect to IDO expression and localization in melanoma brain metastases but also in matched metastases at extracranial sites to correlate intra- and interpatient data with therapy response and survival. Comparative tissue analysis identified macrophages/microglia as the major source of IDO expression in melanoma brain metastases. In contrast to the tumor infiltrating lymphocytes, melanoma cells per se exhibited low IDO expression levels paralleled by cell surface presentation of PD-L1 in intracranial metastases. Absolute numbers and pattern of IDO-expressing cells in metastases of the brain correlated with recruitment and localization of CD8+ T cells, implicating dynamic impact on the regulation of T cell function in the brain parenchyma. However, paired analysis of matched intra- and extracranial metastases identified significantly lower fractions of cytotoxic CD8+ T cells in intracranial metastases while all other immune cell populations remain unchanged. In line with the already established clinical benefit for PD-L1 expression in extracranial melanoma metastases, Kaplan-Meier analyses correlated PD-L1 expression in brain metastases with favorable outcome in advanced melanoma patients undergoing immune checkpoint therapy. In summary, our data provide new insights into the landscape of immunosuppressive factors in melanoma brain metastases that may be useful in the implication of novel therapeutic strategies for patients undergoing cancer immunotherapy.